51.7k views
5 votes
Please help!!!!!
Solve the equation 5(2y - 1) - 2(3y)= 1


User Aslawin
by
6.1k points

1 Answer

0 votes

Answer:

y = 3/2

Explanation:

5(2y - 1) - 2(3y) = 1

First we use distributive property:

10y - 5 - 6y = 1

because 5 × 2y = 10y

and -2 × 3y = -6y

Now we combine the like terms:

4y -5 = 1

because 10y - 6y = 4y

Now we have to send the -5 to the other side. (when we send it to the other side it becomes positive because right now it is negative)

4y = 1 + 5

Again we combine the like terms:

4y = 6

(because 5 + 1 = 6)

Now we have to send the 4 to the other side because we need to get the y value. (when we send it to the other sidr it will be divided)

y = 6/4

and we simplify:

y = 3/2

And we cannot simplify or do anything else. So that is the answer.

Hope that helped!

User ItzMEonTV
by
5.9k points